Engineer versus the volcano. - Patel, P.
He tracks the weird and vivid bursts of lightning from erupting volcanoes. Late one night last March, the icy peak of Mount Redoubt in south central Alaska erupted, sending thick plumes of ash and steam more than 10 000 meters into the air. It was a nightmare for local residents and pilots but a dream come true for Ronald Thomas.